Agroclimatic monitoring system at Alliance’s experimental campus - Barrios, Camilo; Amaya, Alejandra; Arce, Daniela; Urdinola, Jaime (2025)
At the Alliance’s experimental campus, extreme climate conditions such as droughts, heavy rainfall, and high temperatures can signiﬁcantly affect both the management and the growth and development of crops. In this context of increasing climate variability, it is essential to have accessible and easy-to-use digital tools that support technical decision-making in the ﬁeld. These digital tools allow for more efficient planning and management of resources available to farmers. Satellite imagery is leveraged to enable regular monitoring of agroclimatic conditions and crop status without needing to be physically present in the ﬁelds. Speciﬁcally, high-resolution multispectral images, such as those provided by PlanetScope satellites, help detect water excesses or shortages in a timely manner and assess the health, growth, and development of vegetation. This not only optimizes agricultural management but also promotes more sustainable and resilient production in the face of climate change.